Laboratory Investigations on Pervious Concrete for Pavement Construction. - Akampurira, Asaph (Kabale University, 2023)
Pervious concrete is a tailored-property concrete with high water permeability which allow the passage of water to flow through easily through the existing interconnected large pore structure. This study presents the influence of fine aggregate and coarse aggregate quantities on the properties of pervious concrete with the known angularity number of coarse aggregates. Materials used are OPC Type I, sand as fine aggregate corresponding to grading II and four sizes of coarse aggregate namely, 5mm to 6.3mm, 6.3mm to 10mm, 10mm to 14mm, 14mm to 20mm. Mixes were prepared with the water cement ratio of 0.34, cement content of 400kg/m3 and maintaining the cement-aggregate ratio as 1:4.75. Coarse aggregates were replaced with fine aggregate in the percentages of 0%. 10%, 20%, 30%, 40% and 50 % by weight. Various mechanical properties of the mixes were evaluated. Coefficient of permeability was determined by using falling head permeability method. The relationship between the strength, permeability and total void present in aggregate based on angularity number has been developed. Suitability of pervious concrete as a pavement material was discussed.